Innovation and Spin-off Formation in the Public Sector: The BBC Experience - Farr, Timothy (2013)
This paper advances understanding of innovation and spin-off formation in public sector organisations, using BBC loudspeaker development as a case study. It expands and challenges existing theory relating to these two phenomena through the investigation of this case study, which includes the study of various BBC-related companies or spin-offs – namely KEF, Rogers, Harbeth, Spendor and Chartwell. It offers an extensive business history into loudspeaker design innovation over a forty year period, in addition to a comprehensive insight into these aforementioned spin-offs. This paper also contains a review of evidence examining these theories, with particular focus provided on the motivating factors and subsequent degrees of success relating to spin-off formation and public sector innovation.